Fizjoprofilaktyka jako świadczenie zdrowotne w opinii przedstawicieli zawodów medycznych - Czechowska, Beata; Karbowiak, Marta; Siciński, Piotr (Kultura-Społeczeństwo-Edukacja, 2025)
Physioprophylaxis is a health service provided by physiotherapists as part of their professional work. The main aim of physioprophylaxis is to prevent, slow down or reverse the effects of disease and abnormal lifestyles. A total of 563 medical professionals participated in the study, including 458 women and 105 men. Data were obtained using a proprietary survey questionnaire using the PAPI method. The vast majority of respondents have not encountered the very concept of physioprophylaxis in their professional work. Among those over 40, awareness of the term is twice as low as among younger people. More than half of the respondents (59%) could not identify what the term refers to.